The Effects of Future Time Perspective on Self-Regulation in Learning Mediated by Mindfulness - Khoiri, Miftahu Fajar; Purwanto, Edy; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2023)
Self-regulation is a significant thing to achieve better learning process. Therefore, students with low self-regulation will find it hard to manage their time, be passive, and lazy during the learning process. In this, mindfulness was verified to mediate the relationship between future time perspective on self-regulation in learning. This correlational study involved 347 students sampled using a simple random sampling technique, while the data analysis was carried out using bias corrected bootstrapping. Findings revealed that future time perspective predicted mindfulness, self-regulation in learning, while mindfulness predicted self-regulation in learning. Lastly, it was found future time perspective could increase self-regulation in learning through mindfulness. The findings imply the importance of realizing self-awareness for students in terms of psychology and behavior in the learning process.